Vibration of the weapon system on an unmanned ground vehicle during movement - Bui, Viet Dung; Macko, Martin; Dang, Ba Ngoc; Pham, Huu Nguyen (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The article presents a mathematical model of the vibration of a weapon mount on a small unmanned ground vehicle (UGV) with a total weight of up to 70 kg, including the weapon. The design of these small vehicles is similar to that of larger combat vehicles: a mount is placed on a wheeled or tracked chassis, allowing the weapon to be elevated and azimuthally adjusted, and if it allows firing while moving, the angular position of the barrel is affected by chassis vibration and should be stabilized. The vibration of the chassis and parts of the weapon mount is not desirable, and the results of vibration simulation allow for the design of a solution that will eliminate it. Methods: A system of differential equations describing the vibrations of the weapon system and a system of equations describing the motion of the vehicle over terrain were created. Subsequently, the vibrations were simulated in Matlab-Simulink software. Further testing was carried out to measure the deviation of the camera axis from the center of the target. The results of the experiment were compared with the results of the simulation. Results: The research results indicate that the vibration of the weapon system on unmanned ground vehicles depends on many factors, such as the road surface profile, tire properties, suspension system, and overall dimensions, layout, and weight of components. The experimental results of camera stability measurements during target tracking correspond to the simulation results in Matlab-Simulink software. Conclusion: The system of mathematical differential equations of an unmanned ground vehicle, together with the road profile model, describes the factors affecting the vibration of the weapon system during vehicle movement. Mathematical models allow for parameter changes and thus enable simulation of changes in the angular position of the barrel for other input conditions.